Adaptive Coping, Resilience, and Absence of Anxiety Among Displaced Disaster Survivors. [article]. - Docena, P.S.
This study examined the relationships among adaptive coping, individual resilience, community resilience, and absence of anxiety among internally displaced survivors. Household interviews were conducted among 200 survivors of Super Typhoon Haiyan living in a resettlement area in Tacloban City 15 months after they were displaced from their homes. Rather than focusing on trauma, this study took a more positive and agentic approach using the conservation of resources theory as frame. Correlational analyses revealed a significant relationship between adaptive coping and individual resilience, adaptive coping and community resilience, and individual resilience and community resilience. Regression analyses also showed that individual and community resilience each uniquely predicted absence of anxiety among disaster survivors. Implications for practice are discussed, specifically the potential value of interventions that not only nurture individual resilience but also enable community resilience.
Keywords: Disaster; Resilience; Coping; Displaced survivors; Super Typhoon Haiyan